The modulatory effect of infusions of green tea, oolong tea, and black tea on gut microbiota in high-fat-induced obese mice. Issue 12 (4th November 2016) - Liu, Zhibin; Chen, Zhichao; Guo, Hongwen; He, Dongping; Zhao, Huiru; Wang, Zhiyao; Zhang, Wen; Liao, Lan; Zhang, Chen; Ni, Li
Abstract : Tea consumption has been identified to have a gut microbiota modulatory effect, which may be related to its anti-obesity effect. Abstract : Tea consumption has been identified to have an anti-obesity effect. Whether it is associated with gut microbiota modulation is investigated in this study. Phenolic profiles of infusions of green tea, oolong tea and black tea were comprehensively compared first, by utilizing ultra-performance liquid chromatography-electrospray ionization-quadrupole time-of-flight mass spectrometry (UPLC-ESI-Q-TOFMS). Subsequently, high-fat-diet induced obese C57BL/6J mice were orally administered these three types of tea infusions for 13 weeks to evaluate their anti-obesity and gut microbiota modulatory effects. In general, 8 phenolic acids, 12 flavanols, 9 flavonols, 2 alkaloids and 1 amino acid were identified from the three types of tea infusions. Though they possess diverse phenolic compounds, no significant differences in the prevention of the development of obesity in high-fat-fed mice were discovered among the three types of tea. Based on high-throughput MiSeq sequencing and multivariate statistical analysis, it was revealed that tea infusion consumption substantially increased diversity and altered the structure of gut microbiota. The linear discriminant analysis effect size algorithm identified 30 key phylotypes in response to high-fat diet and tea, including Alistipes, Rikenella, Lachnospiraceae, Akkermansia, Bacteroides, Allobaculum, Parabacteroides, etc . Moreover, Spearman's correlation analysis indicated that these key phylotypes might have a close association with the obesity related indexes of the host. This study provides detailed information regarding the impact of tea consumption on gut microbiota, which may be helpful in understanding the anti-obesity mechanisms of tea.